A spatial perspective of the population structure and connectivity of two small tuna species, Katsuwonus pelamis (Skipjack tuna) and Euthynnus affinis (Kawakawa), in the Southwest Indian Ocean - Taylor, Christopher John (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Katsuwonus pelamis and Euthynnus affinis are two small tuna species of socio-economic and fisheries importance across the Southwest Indian Ocean (SWIO). There is currently a dearth of data and information around various aspects of their biology in the SWIO, including their population structure and connectivity. The availability of such data, including spatially represented biological data, has the potential to address current management discrepancies through the provision of more robust assessments into the stock structure and connectivity of these species and their stocks. This study explored a spatial perspective of the population structure and connectivity of K. pelamis and E. affinis fisheries in the SWIO to determine the suitability of current Indian Ocean Tuna Commission (IOTC) management measures for the species. It employed two primary data sources: a) Western Indian Ocean Marine Science Association's (WIOMSA) Marine and Coastal Science for Management (MASMA) Project and b) IOTC. WIOMSA MASMA and IOTC data was collected throughout many countries and small island states in the SWIO, and pertained to genetic diversity, catch-weight, length-at-maturity, and morphometrics. Such data were combined and analysed to conduct geospatial analysis. Spatially illustrated genetic divergence, length-at-maturity, catch-weight, and morphometric data supported the presence of three reproductively isolated subpopulations of K. pelamis in the SWIO (Dar es Salaam, Tanzania, and Kenya; Mtwara, Tanzania, Mozambique, and Eastern Cape, South Africa; Seychelles). Only spatially depicted genetic divergence data, and morphometrics, supported that E. affinis populations were not panmictic in the SWIO, with genetic divergence data supporting the presence of three reproductively isolated subpopulations of E. affinis (Northern Mozambique and Kenya; Tanzania; Seychelles). Spatially illustrated length-at-maturity and catch-weight data however did not provide sufficient evidence supporting spatial structuring among E. affinis populations in the SWIO. Whilst the present analyses are not definitive to delineate exact stock boundaries, findings supported the contention of current IOTC management policy, indicating spatial population complexity for both species. Future research must increase representation of fishery independent samples and must investigate oceanographic variables driving potential stock separation to further support effective management reform. Until available, a precautionary approach should be adopted for the management of these species across the SWIO, considering the presently proposed distribution of their stocks separate for management.
Keywords: Fishery management -- Indian Ocean Region; Geospatial analysis; Skipjack tuna; Euthynnus affinis; Fish populations -- Indian Ocean Region; Marine fishes -- Geographical distribution